Auditoría Financiera a la Cooperativa de Transporte Mixto Puerto Hualtaco del Cantón Huaquillas, período 2021 - Sarmiento Ramírez, Ariana Lisseth (2023)
The present Work of Curricular Integration called "Financial Audit to the Cooperative of Mixed Transport Puerto Hualtaco del Canton Huaquillas, period 2021" was developed as a prerequisite to opt for the degree of Bachelor in Accounting and Auditing, raising the following objectives: To evaluate the internal control in order to guarantee the administrative compliance according to the pre-established in the Norms, Laws and Regulations; To determine the reasonableness of the accounting balances of the components that integrate the Financial Statements; To elaborate a Financial Audit report and Professional Opinion that serves for the correct decision making. For the development of the Financial Audit was carried out in accordance with its three audit phases, PHASE I Planning a previous visit was made to the Cooperativa de Transporte Mixto Puerto Hualtaco, in order to collect timely information that allows to know the entity, then internal control evaluations were made to each of the components that make up the financial statements in order to determine the level of risk and reasonableness of the balances presented, verifying compliance with current regulations and Generally Accepted Accounting Principles; PHASE II Execution of the work, tests and procedures were applied to the items Assets, Equity, Income and Expenses; PHASE III Communication of Results a report and professional opinion was issued containing comments, conclusions and recommendations to correct the deficiencies found, such as: bank reconciliations are not performed; accounts receivable are not collected on their due date, causing untimely recording; no physical verification; assets without codification; no personnel responsible for assets; untimely recording of income and expenses; no orderly filing of supporting documentation.